2019
DOI: 10.1002/jbmr.3925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Advanced Glycation End-Products (AGE) Lowering Drug ALT-711 on Biochemical, Vascular, and Bone Parameters in a Rat Model of CKD-MBD

Abstract: Chronic kidney disease–mineral bone disorder (CKD‐MBD) is a systemic disorder that affects blood measures of bone and mineral homeostasis, vascular calcification, and bone. We hypothesized that the accumulation of advanced glycation end‐products (AGEs) in CKD may be responsible for the vascular and bone pathologies via alteration of collagen. We treated a naturally occurring model of CKD‐MBD, the Cy/+ rat, with a normal and high dose of the AGE crosslink breaker alagebrium (ALT‐711), or with calcium in the dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…(53) Moreover, a recent study in CKD rats (n = 56) treated with an AGE breaker, alagebrium, showed reduced total bone AGE content but no difference in bone pentosidine levels, which again points to the heterogeneity in AGEs and limitations of measuring one AGE as a representative of whole group. (54) In sex-stratified analysis for fractures, there was an association of SAF with MOFs only in women but not in men, but no such difference for VFs. Notably in our cohort, the prevalence of MOFs in women is four times higher than in men, which may partly explain this difference.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 90%
See 1 more Smart Citation
“…(53) Moreover, a recent study in CKD rats (n = 56) treated with an AGE breaker, alagebrium, showed reduced total bone AGE content but no difference in bone pentosidine levels, which again points to the heterogeneity in AGEs and limitations of measuring one AGE as a representative of whole group. (54) In sex-stratified analysis for fractures, there was an association of SAF with MOFs only in women but not in men, but no such difference for VFs. Notably in our cohort, the prevalence of MOFs in women is four times higher than in men, which may partly explain this difference.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 90%
“…( 53 ) Moreover, a recent study in CKD rats ( n = 56) treated with an AGE breaker, alagebrium, showed reduced total bone AGE content but no difference in bone pentosidine levels, which again points to the heterogeneity in AGEs and limitations of measuring one AGE as a representative of whole group. ( 54 )…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that reduction of total bone AGE using the AGE cross‐link breaker failed to improve bone mechanical properties in animals with chronic kidney injury. ( 38 ) We assume they failed because AGE accumulation is not the only pathophysiological mechanism underlying deteriorated bone elastic mechanical properties associated with chronic kidney injury, as this study demonstrated.…”
Section: Discussionmentioning
confidence: 74%
“…Studies show that NOX2 play a critical role in AGEs-induced ROS production and endothelial dysfunction [ 30 , 31 ]. In the present study, we also observed a significant increase of NOX2 expression in the aortas of db/db mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%